Terpaan Media Nature Republic with NCT 127 terhadap Brand Image: Studi Kasus Iklan Nature Republic pada Youtube - Febriana Muflika Sari; Riska Tyas Prahesti (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Advertising is one of the forms of external cyber public relations carried out by companies in promotion both through mass media and sosial media. Technological advances have created new forms of interaction and sosialization, one of which is the innovation of communication technology in the form of sosial media. One of the most popular and trending sosial media is YouTube. Advertising is an effective form of promotion of a product or service by using sosial media YouTube as done by Nature Republic. Nature Republic used youtube to promote and introduce the Brand Ambassador NCT 127 in improving the Brand image through the display of an advertisement Nature Republic with NCT 127, on youtube in wide coverage, and better known by the public. As far as the formula of the problem of this study is to find out how much influence the media nature republic with NCT 127 on the Brand image nature republic study of the case of the display of Advertising Nature Republic with NC T 127 on sosial media Youtube. The study uses a quantitative method with an approach to the survey method, using Taro Yamane to obtain the sample with a total of 83 respondents, non-probability sampling techniques, while data collection techniques use the distribution of questionnaires through googleform. The results show that there is a positive and significant influence between media influence on Brand image and moderate influence.